The Future of Leadership Framework in Malaysia Education Systems - Mat Nashir, Irdayanti; Esti, Dwi; Nazirah Mohd Imam Ma’arof, Nurul; Nor Azhari bin Azman, Mohamed; Khairudin, Moh (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to discover the perspective of the Technical and Vocational Education and Training (TVET) experts on the innovative instructional leadership. The methodological approach used in developing the questionnaires is the Modified Delphi Technique. For this purpose, the interviews with 11 experts were conducted to obtain the data analysis. Next, the results obtained were analyzed using exploratory factor analysis (EFA) to acquire the constructs and items prior to technical and vocational education leadership. Based on the findings of the analysis result, 13 out of 17 constructs that were proposed in the beginning of the interview were found. Researchers hope the findings of these constructs will improve the leadership performance among the technical and vocational leaders in leading TVET organizations as the center of attention in the future.